FRI0479 REWIRED CELL ENERGY METABOLISM IN A NOVEL KRAS-MUTATED HISTIOCYTOSIS CHARACTERIZED BY SEVERE SYNOVITIS. (2nd June 2020) - Cavalli, G.; De Luca, G.; Biavasco, R.; Nemkov, T.; D'alessandro, A.; Arts, R.; Villa, A.; Belloni, D.; Grassini, G.; Cangi, G.; Doglioni, C.; Ferrero, E.; et al.
Abstract : Background: Histiocytoses are disorders characterized by tissue infiltration by macrophages, dendritic cells, or monocyte-derived cells. These diseases are classified in five groups based on histologic, clinical, and molecular features: Langerhans-related, cutaneous/mucocutaneous and malignant histiocytoses, Rosai-Dorfman disease, and hemophagocytic lymphohistiocytosis (1). Langerhans-related histiocytoses comprise Langerhans cell histiocytosis and Erdheim-Chester disease, both inflammatory myeloid-driven diseases characterized by clonal activating mutations along the MAPK or related pathways, most commonly BRAF V600E, and by severe tissue and systemic inflammation (2). Here, we describe and characterize a novel, related histiocytosis chiefly manifested with severe synovial involvement. Objectives: Here, we describe a novel histiocytosis whose histologic and clinical picture (severe synovial involvement, systemic inflammation, skin lesions, and diabetes insipidus) differed from known histiocytic disorder. In addition, we performed molecular studies aimed at identifying causative activating mutations. Finally, by means of a dynamic 3D tissue culture system we characterized immune-metabolic mechanisms underlying disease pathogenesis and clinical response to treatment. Methods: The mutational status of oncogenes was determined with a mass spectrometry multiplexed genotyping approach (PentaPanel). Biospy samples were cultured in RCCSTM bioreactor (Synthecon) in the presence/absence of a MEK inhibitor (GSK1120212, 1nM), and then either processed for immunohistochemical analyses, or lysed for western blot analysis. Culture supernatants were collected for cytokine, chemokine and metabolome determination. The Bio-Plex Multiple-Cytokine Assay (Bio-Rad) and the Ella assay (ProteinSimple) were used to determine cytokine concentrations in supernatants and serum, respectively. Metabolomic studies were performed as described (3). Results: We identified a causative mutation in the proto-oncogene KRAS ( KRAS G12D, not previously reported in related histiocytoses). In addition, 3D culture studies of patient's biopsies revealed KRAS-driven signaling, phenotypic, and immunometabolic features. These included constitutive ERK and AKT phosphorylation, up-regulated glucose metabolism with glycolysis and TCA cycle activation, and deregulated release of pro-inflammatory cytokines IL-1β, IL-6 and TNFα. All these features reverted upon pharmacologic inhibition of the MAPK pathway. Characterization of this novel condition instructed effective treatment of the patient with the MEK inhibitor cobimetinib. Conclusion: Genetic, clinical, and histopathology features differentiate this condition from known histiocytic disorders. Mechanistically, KRAS G12D causes constitutive activation of the MAPK pathway in macrophages, which results in maladaptive changes in cell energy metabolism sustaining rampant production of pro-inflammatory cytokines. Besides instructing effective treatment of this patient, these studies revealed metabolic rewiring as key to pathologic inflammatory activation of macrophages in human disease. References: [1]Emile JF, et al. Revised classification of histiocytoses. Blood. 2016 [2]Cavalli G, et al. The multifaceted clinical presentations and manifestations of Erdheim-Chester disease. Ann Rheum Dis. 2013 [3]Cavalli G, et al. Interleukin 37 reverses the metabolic cost of inflammation, increases oxidative respiration, and improves exercise tolerance. Proc Natl Acad Sci U S A. 2017 Disclosure of Interests: Giulio Cavalli Consultant of: SOBI, Pfizer, Sanofi, Novartis, Paid instructor for: SOBI, Novartis, Speakers bureau: SOBI, Novartis, Giacomo De Luca Speakers bureau: SOBI, Novartis, Celgene, Pfizer, MSD, Riccardo Biavasco Employee of: Bluebird, Travis Nemkov: None declared, Angelo D'Alessandro: None declared, Rob Arts: None declared, Antonello Villa: None declared, Daniela Belloni: None declared, Greta Grassini: None declared, Giulia Cangi: None declared, Claudio Doglioni: None declared, Elisabetta Ferrero: None declared, Marina Ferrarini: None declared, Lorenzo Dagna: None declared